Addressing the Reliability and Security of LLMs usage with an Integrated Information Science and NLP Architecture - Brito, Bruno H.; Santos, Roney L. de S. (Anais do Workshop em Desempenho de Sistemas Computacionais e de Comunicação (WPerformance); 2026: Anais do XXV Workshop em Desempenho de Sistemas Computacionais e de ComunicaçãoDO - 10.5753/wperformance.2026.22012, 2026)
This research addresses organizational data transformation by integrating Information Science (IS) and Natural Language Processing (NLP).We argue that Large Language Model (LLM) failures in data interaction tasks (instantiated via text-to-sql), such as hallucinations, stem from applications detached from information governance. We propose an interdisciplinary architecture employing a Knowledge Graph as an Intelligent Proxy to centralize metadata and ontologies. Validation through nine use cases demonstrates the architecture is functionally effective, generating accurate database queries matching ground-truth and identifying invalid relationships without exposing raw transactional data to the LLM.